2016
DOI: 10.1002/cctc.201600942
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Aerial Oxidation of Biomass‐Derived Furans to Furan Carboxylic Acids in Water over Bimetallic Nickel–Palladium Alloy Nanoparticles

Abstract: Bimetallic Ni1−xPdx (0.10≤x≤0.75) alloy nanoparticle catalysts were synthesised and successfully employed for the catalytic aerial oxidation of biomass‐derived furans, such as 2‐furfuraldehyde (furfural), 2‐furfuryl alcohol (furfuryl alcohol), 5‐hydroxymethyl‐2‐furfural (5‐HMF), 5‐methyl‐2‐furfural (MF) and 5‐methyl‐2‐furfuryl alcohol (MFA), to selectively afford the corresponding furan carboxylic acids (2‐furoic acid, furan‐2,5‐dicarboxylic acid (FDCA) and 5‐methyl‐2‐furoic acid (MFCA)) in water at 80 °C. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 77 publications
(219 reference statements)
1
31
0
Order By: Relevance
“…[198] Recently,w ee xplored oxidation of biomass-derived furans (furfural and HMF) over bimetallic Ni 1Àx Pd x (0.10 x 1) using air as an oxidizing agent. [200] We demonstrated that by tuningt he Ni to Pd contentsi nt he bimetallic Ni 1Àx Pd x catalyst, catalytic efficacy of Ni 1Àx Pd x catalysts towards the oxidation of furans can be controlled. It was observed that by decreasingt he Pd content in the bimetallic Ni 1Àx Pd x catalyst higher catalytic activity can be achieved,a nd hence,N i 0.90 Pd 0.10 exhibited the highest catalytic activity among all the studied catalysts.…”
Section: Catalytic Oxidation Of Biomass-derived Furfural and Hmf Overmentioning
confidence: 91%
See 1 more Smart Citation
“…[198] Recently,w ee xplored oxidation of biomass-derived furans (furfural and HMF) over bimetallic Ni 1Àx Pd x (0.10 x 1) using air as an oxidizing agent. [200] We demonstrated that by tuningt he Ni to Pd contentsi nt he bimetallic Ni 1Àx Pd x catalyst, catalytic efficacy of Ni 1Àx Pd x catalysts towards the oxidation of furans can be controlled. It was observed that by decreasingt he Pd content in the bimetallic Ni 1Àx Pd x catalyst higher catalytic activity can be achieved,a nd hence,N i 0.90 Pd 0.10 exhibited the highest catalytic activity among all the studied catalysts.…”
Section: Catalytic Oxidation Of Biomass-derived Furfural and Hmf Overmentioning
confidence: 91%
“…Furthermore, Pd nanoparticles supported on Mg‐Al‐CO 3 hydrotalcite (Pd/HT) are also explored for an efficient catalytic oxidation of HMF to FDCA in water in the absence of any base additive . Recently, we explored oxidation of biomass‐derived furans (furfural and HMF) over bimetallic Ni 1− x Pd x (0.10≤ x ≤1) using air as an oxidizing agent . We demonstrated that by tuning the Ni to Pd contents in the bimetallic Ni 1− x Pd x catalyst, catalytic efficacy of Ni 1− x Pd x catalysts towards the oxidation of furans can be controlled.…”
Section: Catalytic Oxidation Of Biomass‐derived Furfural and Hmf Overmentioning
confidence: 99%
“…Synthesis of furan‐2‐carboxylic acid (2‐furoic acid) (L7) . The biomass derived furan derivative, furan‐2‐carboxylic acid (2‐furoic acid) was prepared by following the reported procedure using Ni 0.90 Pd 0.10 nanoparticles as a catalyst . A two‐neck round‐bottom flask was charged with freshly prepared 5 mol‐% Ni 0.90 Pd 0.10 nanoparticles followed by the addition of furan 2‐carboxyaldehyde (1 mmol, 82.8 µL).…”
Section: Methodsmentioning
confidence: 99%
“…The overall FDCA yield reached 53 %. Recently, a two‐step process for the conversion of fructose into FDCA was reported . In the first step, fructose was treated with 0.5 equivalents of NH 4 Cl in 2‐propanol at 353 K for 12 h. Then, water and 1.5 equivalents of Na 2 CO 3 were added to the mixture for further reaction at 353 K, with air bubbling through the solution in the presence of a Ni−Pd nanoparticle catalyst.…”
Section: Conversion Of Cellulose Into Dicarboxylic Acidsmentioning
confidence: 99%